2020
DOI: 10.15567/mljekarstvo.2020.0305
|View full text |Cite
|
Sign up to set email alerts
|

Effects of starter culture and storage on volatile profiles and sensory characteristics of yogurt or cream butter

Abstract: In this study volatile compounds and sensory properties of butter produced from cream or yogurt using Lactococcus lactis subsp. lactis biovar. diacetylactis or Leuconostoc mesenteroides subsp. cremoris as well as a mixture of these two bacteria were investigated over 60 days. A total of 10 esters, 6 aldehydes, 11 ketones, 16 alcohols, 6 acids, 2 sulphides, 3 terpenes, and 3 miscellaneous compounds were detected. There were more volatile compounds in cream butter than in yogurt butter. While S-methyl thioacetat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 33 publications
0
2
1
Order By: Relevance
“…96/2011). These results are higher than the findings reported by Gundogdu et al (2019). Also, the opposite to previously research butter made from cream had lower total solids than yoghurt samples.…”
Section: Chemical Composition and Peroxide Degreecontrasting
confidence: 94%
“…96/2011). These results are higher than the findings reported by Gundogdu et al (2019). Also, the opposite to previously research butter made from cream had lower total solids than yoghurt samples.…”
Section: Chemical Composition and Peroxide Degreecontrasting
confidence: 94%
“…Cream is the main raw material to produce butter and reflects its properties in butter quality. Cream fermentation with starter cultures impacts the physicochemical and sensory properties of butter and influences its nutritional composition, texture and shelf life [14,15]. Usually, cream undergoes fermentation with mesophilic lactic acid bacteria, namely Lactococcus lactis ssp.…”
Section: Introductionmentioning
confidence: 99%
“…The present work identified S -methyl thioacetate, ethyl (methylthio) acetate, dimethyl disulfide, 2-methylthiophene, 3-methylthiophene, and dimethyl trisulfide in Ponkan mandarin juice for the first time. Furthermore, according to the previous studies, S -methyl thioacetate, with a cabbage-like odor, was also found in oolong tea, yogurt, and Chinese liquor, representing a degradation product of l -leucine and l -valine . Ethyl (methylthio) acetate with a green odor is always found in many fruits such as durian, mango, and melon .…”
Section: Resultsmentioning
confidence: 75%